PERAN BERBAGI PENGETAHUAN TERHADAP KINERJA INDIVIDU DAN KINERJA ORGANISASI - Nurofi, Achmad (STIE Totalwin Semarang, 2013)
This paper explores the relationship between knowledge sharing, organizational and individual performance. First, it is argued that knowledge sharing should be associated with individual performance, second that individual performance and organizational performance are strongly associated to each other. Next, the conceptual relationship between knowledge sharing, individual performance and organizational performance has been established. After that, corresponding prepositions on knowledge sharing individual performance and its relationship on organizational performance has been given. This study adds to the understanding of the effects of knowledge sharing on individual and organizational performance, and gives implications to the practice of knowledge sharing